EARTHQUAKE TRIGGERING EFFECT SCENARIOS DURING THE 2014 SEQUENCE IN CEPHALONIA AND 2015 EARTHQUAKE IN LEFKADA BROADER AREAS, IONIAN SEA, GREECE - Sboras, S.; Chatzipetros, A.; Pavlides, S.; Karastathis, V.; Papadopoulos, G. (Bulletin of the Geological Society of Greece, 2016)
In this paper we defined the local complex fault system of the Cephalonia three strongest earthquakes (Mw6.1, Mw5.3 and Mw6.0) of the January-February 2014 sequence and the Lefkada mainshock (Mw6.4) on November 17, 2015, in order to investigate the fault interaction i) within the 2014 sequence, ii) between the 2014 sequence and the fault that produced the 2015 Lefkada event, and iii) the cumulative effects of all Cephalonia and Lefkada strong events on other neighbouring faults, by calculating the static stress changes. The Coulomb stress change calculations suggest a complex distribution pattern on most of the cases, with only exceptions the F4 fault (Lefkada earthquake), which seems to be barely loaded with stress after the Cephalonia 2014 events, and the “Assos-Skala” fault, which seems to be stress relieved after all Caphalonia 2014 and Lefkada 2015 events.